Codon Optimization Significantly Improves the Expression Level of α-Amylase Gene from Bacillus licheniformis in Pichia pastoris. - Wang, Jian-Rong; Li, Yang-Yuan; Liu, Dan-Ni; Liu, Jing-Shan; Li, Peng; Chen, Li-Zhi; Xu, Shu-De (BioMed Research International, 2015)
α-Amylase as an important industrial enzyme has been widely used in starch processing, detergent, and paper industries. To improve expression efficiency of recombinant α-amylase from Bacillus licheniformis (B. licheniformis), the α-amylase gene from B. licheniformis was optimized according to the codon usage of Pichia pastoris (P. pastoris) and expressed in P. pastoris. Totally, the codons encoding 305 amino acids were optimized in which a total of 328 nucleotides were changed and the G+C content was increased from 47.6 to 49.2%. The recombinants were cultured in 96-deep-well microplates and screened by a new plate assay method. Compared with the wild-type gene, the optimized gene is expressed at a significantly higher level in P. pastoris after methanol induction for 168 h in 5- and 50-L bioreactor with the maximum activity of 8100 and 11000 U/mL, which was 2.31- and 2.62-fold higher than that by wild-type gene. The improved expression level makes the enzyme a good candidate for α-amylase production in industrial use.